Using Zeolites to Cold Stabilize White Wines - Tim Reilly; Pawel Mierczynski; Andri Suwanto; Satriyo Krido Wahono; Waldemar Maniukiewicz; Krasimir Vasilev; Keren Bindon; Agnieszka Mierczynska-Vasilev (Australian Journal of Grape and Wine Research, 2023)
Background and Aims. Tartrate stabilisation is a necessary step in commercial wine production. The traditional method to prevent crystallisation and precipitation of potassium bitartrate (KHT) after a wine is bottled is by adding seed KHT crystals to wine stored in a tank and holding temperatures below 0°C for a set period of time before bottling. This process requires time and energy and a filtration step to remove sediment. However, compared to other technical solutions such as reverse osmosis, electrodialysis, or ion exchange, it is still the most economical stabilisation option. This work aims to evaluate the ability of zeolites to cold stabilize white wines. Since zeolites can also remove proteins and thus heat-stabilize white wines, the new process can potentially combine heat and cold stability in a single treatment. Methods and Results. Effective tartrate stabilisation was achieved by mixing a natural zeolite sample with white wine for three hours. Although the quantum of required zeolite was larger than bentonite, zeolite did not exhibit shrink-swell behaviour, thus enabling greater wine recovery and capacity to be regenerated. Effective heat and cold stability could be achieved using a low-calcium zeolite as a processing aid in a single treatment. To avoid aluminium leaching and elevated aluminium concentrations in the treated wine, the zeolite was calcinated before being added to the wine. The calcination process also reduced calcium content in the wine after treatment with zeolite, thus eliminating the risk of calcium instability. Conclusions. The application of zeolite as a processing aid can potentially be effective in cold-stabilizing white wines and removing proteins responsible for haze formation. Significance of the study. Zeolites may constitute an alternative technology in white wine production facilitating heat and cold stabilisation in a single treatment.